Level of Knowledge and Experience of Pregnant Women with Disaster Preparedness at The Kemayoran District Community Health Center - Febri Annisaa Nuurjannah (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Indonesia is one of the countries in the world that is very vulnerable. experience disaster. Incident disaster dominated by disasters hydrometeorology, one of them that is disaster floods that caused high number of missing and deceased people. Based on data from the National Disaster Management Agency Disaster Management Agency (BNPB) in 2021 disaster Floods in DKI Jakarta caused 16 disasters. Research This aim For Know Level of Knowledge and Experience of Pregnant Women with Disaster Preparedness at Community Health Centers Kemayoran District. The method study This that is use method descriptive quantitative with approach cross sectional with analytical survey at the Community Health Center Kemayoran in One time. Population in the study This is all over Mother pregnant who undergo visit pregnancy at the Community Health Center Kemayoran District, which has 63 people with sample the entire total population. The data was analyzed use independent chi-square with level 95% confidence and presented in distribution table form frequency. Obtained results there is relationship between level of knowledge and experience with preparedness face disaster flooding in the mother pregnant at the Community Health Center Kemayoran . It is hoped Health workers at Kemayoran Health Center can motivate the cadres integrated health posts and figures public For increase Study together, discuss and exchange experience about Preparedness Facing Disaster Flood To mother pregnant comprehensive and systematic as well as can be implemented in a way scheduled and continuous.